2019
DOI: 10.1002/mp.13432
|View full text |Cite
|
Sign up to set email alerts
|

Performance of long rectangular semi‐monolithic scintillator PET detectors

Abstract: Purpose: High-sensitivity and high-resolution depth-encoding positron emission tomography (PET) detectors are required to simultaneously improve the sensitivity and spatial resolution of a PET scanner so that the quantitative accuracy of PET studies can be improved. The semi-monolithic scintillator PET detector has the advantage of measuring the depth of interaction with single-ended readout as compared to the traditional pixelated scintillator detector, and significantly reducing the edge effect that deterior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 49 publications
0
21
2
Order By: Relevance
“…6 In another work, a semi-monolithic block with 11 rectangular slabs of 1 × 37.6 × 10 mm 3 was studied with different surface treatments. 7 The detector exhibited 1.07 mm spatial resolution in the monolithic direction, 1.55 mm DOI resolution, 24.9% energy resolution (for one slab), and 788 ps timing resolution with black painting. The timing and energy resolutions were improved to 596 ps and 15.8%, respectively, with ESR treatment, but the spatial and DOI resolution worsen to 1.77 mm and 2.71 mm, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…6 In another work, a semi-monolithic block with 11 rectangular slabs of 1 × 37.6 × 10 mm 3 was studied with different surface treatments. 7 The detector exhibited 1.07 mm spatial resolution in the monolithic direction, 1.55 mm DOI resolution, 24.9% energy resolution (for one slab), and 788 ps timing resolution with black painting. The timing and energy resolutions were improved to 596 ps and 15.8%, respectively, with ESR treatment, but the spatial and DOI resolution worsen to 1.77 mm and 2.71 mm, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The LD in the monolithic direction can be characterized, and the DOI information recovered, preserving both the high sensitivity and good spatial resolution of monolithic detectors. 6,7 The effects on the resolvability of slabs with two different reflectors applied to the lateral walls and different light guide thicknesses have been tested elsewhere. 8 There it is shown that the use of light guides and enhanced specular reflector (ESR) improve the resolvability of the slabs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple methods to collimate gamma photons have been used in literature: the most simple method is electronic collimation as no further instrumentation except PET components is needed [29], [30]. However, the beam profile depends on the accuracy the coincidence detector achieves.…”
Section: Introductionmentioning
confidence: 99%